Value Of The Index Of Pulsatilidad Average Of The Uterine Arteries In The Predictions Of Preeclampsia Between 11 And 14 Weeks In Lima - Perú - admin, admin (2018)
Objective. To determine the uterine artery mean pulsatility index and to calculate the predictive value of the uterine artery mean pulsatility index ≥ 95th centile to predict Preeclampsia in pregnant women between 11 y 14 weeks. Lugar. Fetal Medicine Unit at INMP, a teaching Hospital, between May 2009 to March 2010. Materials and methods. Participants. Pregnant women between 11 y 14 weeks.Interventions. Uterine artery Doppler was carried out at 11 y 14 weeks in pregnant women attending for routine antenatal care. The right and left uterine arteries were identified using color flow mapping and velocity waveforms were obtained using pulsed Doppler. Main outcome measures. Determination of the uterine artery mean pulsatility index, identification of ≥ 95th centile, determination of sensibility, specificity, positive and negative predictive value. Results. Of 120 patients enrolled, 24 developed Gestational Hypertension (20%), 6 Mild PE (5%) y 4 Severe PE (3,3%). The value of the uterine artery mean pulsatility index ≥ 95th centile was 2,66. The sensibility of this cut point was 20%, specificity 96%, PPV 33%, NPV 93%, RR (IC 95%) 4,75 (1,28 – 17,68). Conclusion. The uterine artery mean pulsatility index ≥ 95th centile between 11 y 14 weeks of gestation, has an excellent predictive value of Preeclampsia.